Clericalism and Laicism — Two Extremes in the Understanding of the Church Service - Крстић, Зоран Г (Sabornost - The Theological Year-book, 2012)
Author in this paper discusses the exaggeration in understanding the content of church services that have historically often manifested as clericalism, as one sex, and laicism as its opposite. Starting from the clericalism one should point to different forms of which it had been winning throughout history, such as political, social and cultural clericalism. The emphasis in this analysis is that the author considers clericalism in the Church community by seeing its origins and causes of the so-called theory of sanctification, which is manifested in different ways in the Church life of the Western and Eastern Churches. The first consequence of this theory is the change of the term layman in terms of the member of God’s people, by the layman in terms of the world. The second consequence is a lesser or greater passivity of the laity in Church life. He sees the resolution of issues in a revival of the traditional ecclesiology that identifies the service and the gifts of the Holy Spirit, and thus does no separate institutional structure of the charismatic Church. The last part deals with the consequences of laicism in the Church life as a reaction to the excessive clericalism.